IMPLEMENTASI FUNGSI PENGAWASAN BADANPERMUSYAWARATAN DESA (BPD) DALAM MENGAWASI KINERJA KEPALA DESA DI DESA HILIFAROKHALAWA KECAMATAN FANAYAMA KABUPATEN NIAS SELATAN - Ndruru, Primus Bradianto; Pasaribu, Jhonson; Degodona, L. Primawati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Government success depends heavily on the effectiveness of oversight. Effective oversight ensures the smooth implementation of work programs, a key factor. This thesis examines how the Village Consultative Body (BPD)'s oversight mechanism effectively oversees the performance of the Village Head in Hilifarokhalawa Village, Fanayama District, South Nias Regency. The BPD in Hilifarokhalawa Village is obligated to ensure that the village head operates in accordance with regulations and in the interests of the village community. However, the reality on the ground shows that the implementation of this oversight function is not yet optimal. This is evident in persistent community complaints about the village head's performance, the lack of public participation in the decision-making process, and weak communication between the BPD and the village government. These factors can hinder the realization of good and participatory village governance. Home Affairs Ministerial Regulation Number 110 of 2016 serves as a normative framework that clearly regulates the position, duties, functions, authorities, and obligations of the BPD. The regulation explains that the BPD has an oversight function over the performance of the village head, particularly regarding policy implementation, financial management, and strategic decision-making at the village level. Therefore, it is important to assess the extent to which this regulation has been implemented in practice, particularly in Hilifarokhalawa Village. Through this research, the author aims to examine how the Village Consultative Body (BPD) implements its supervisory function in overseeing the performance of village heads, the challenges faced by the BPD, and the efforts that can be made to strengthen its supervisory role. This research is expected to contribute to strengthening the institutional capacity of the BPD and provide input for stakeholders in improving the quality of village governance.